DRUG UTILIZATION STUDY IN GERIATRIC PATIENTS AT RURAL TERTIARY CARE HOSPITAL - Kolhe, Atul; AS, KALE; PADWAL, SUDHIR L (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Abstract Objective: To study the drug utilization pattern in geriatric patients at rural tertiary care hospital. Materials and Methods: Â This was a cross-sectional observational study involving 600 geriatric outpatients. The study was carried out from May 2014 to July 2014. The data was collected using predesigned pro forma specially designed for this purpose. Relevant information was obtained by analyzing the prescriptions for WHO core drug indicators. Results: - The total numbers of prescriptions studied were 600. The total number of drugs prescribed is a product of actual drugs and number of patient prescriptions. The majority of the patients were in the age group 65-70 years (69.33%). There was male preponderance (58.66%). Musculoskeletal diseases were the most common (26.33%), followed by cardiovascular diseases (26%). The average number of drugs per prescription was 2.79. Out of total number of drugs prescribed, 380 drugs (22.64%)Â were prescribed by their generic name and 1298 drugs (77.35%) were prescribed by their brand name. 1308 drugs (77.94%)Â prescribed were from World Health Organization's Essential Medicines List 2011 (WHO-EML). Drugs acting on the cardiovascular system (23.36%) were the most frequently prescribed, followed by vitamins, minerals (18.23%) and drugs acting on the gastrointestinal system (15.73%). Conclusion: Â The study has shown the pattern of diseases prevalent in geriatric patients and drug use among them. Thus drug utilization study can help in assessment and promotion of rational use of drugs Keywords: Drug utilization, geriatric, polypharmacy, rational use.